The Effects Of Giving The Lemuru Fish Oil (Sardinella longiceps) Systemically On The Number Of Osteoblasts In Dental Socket Healing Process - Dwi Surya Sudrajat; Eddy Hermanto; Soemartono*** *Sarjana Kedokteran Gigi Fakultas Kedokteran Gigi Universitas (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: Sockets healing is a dynamic, continuous and overlapping process. Osteoblasts are important cells in healing sockets that will mineralize into bone until the injured tissue heals. Lemuru fish oil (Sardinella longiceps) contains omega 3 which can increase the number of osteoblasts so that it accelerates the process of socket healing after tooth extraction. Purpose: To determine the effect lemuru fish oil that given systemically in increasing the number of osteoblasts in post-extraction tooth socket wound healing. Materials and methods: Experimental research laboratories with post test only control group design. Samples of 33 male Wistar mice were divided randomly into 3 groups. Group K as a control group that was not given lemuru fish oil, group P1 as a group given lemuru fish oil 1.5ml / 200g BB, and P2 group as a group given 1 ml / 200g BB lemuru fish oil. Extraction of left mandibular first incisor was carried out, then extract was given once a day for 7 days with gastric sonde. Observations were made on the 14th day after tooth extraction by calculating the number of osteoblasts in the histology sample using HE (Hematoxylin Eosin). Results: In each treatment group there were significant differences (P <0.05) and significant comparisons (P> 0, 05). Conclusion: Giving lemuru fish oil can increase the number of osteoblasts to post-extraction tooth socket wound healing.